Sistem Pendidikan di Masa Rasulullah Persfektif Al-Qur’an dan Hadis dan Implementasinya Dengan Pendidikan Indonesia - Idghom Mukholik; Tulus Musthofa; Nur Saidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article aims to research the education system during the time of the Prophet and its implementation with education in Indonesia. The aim of this research is to find out the between the education systems implemented during the time of the Prophet prespective of the Qur’an and Hadith and provide implications for education in Indoesia. so that it can be used as a guide and see the development and progress from the time of the Prophet. This research method uses a library method or what is known as (Library Research) where the data or materials needed in research refer to books, journals, magazine documents and so on. The results of the research show that education in the time of the Prophet focused on the spread of Islam. This is divided into 2 parts, namely the Makkah and Medina phases. In the Makkah phase, focus on monotheism, prayer and morals. In the Medina phase, focus on forming leader. Modern era education has adequate capacity because it has technology as an educational tool. With different education system patterns, they have a big impression that they both aim to increase knowledge.